The public administration reform in post-war Bosnia and Herzegovina: A reform process embedded in a sovereignty paradox - Milovich, L.; Ossewaarde, M.R.R. (2013)
As the post-war Bosnia and Herzegovina has turned its interest towards a European Union membership, it has entered an accession process requiring it, among other things, to reform its public administration system. The European Union's involvement within the reform has been placed under critique, as it has been claimed to have placed Bosnia and Herzegovina's sovereignty at risk by presenting contradicting behaviors leading to a sovereignty paradox. By examining the European Union's role in Bosnia and Herzegovina, and its possible relations to a sovereignty paradox in the process, the article finds sovereignty paradox indicators to exist along its processes. - Reproduced.
Keywords: Administrative reform